Avaliação do impacto da moradia estudantil nas variáveis de desempenho, permanência, retenção e evasão dos discentes da Universidade Federal de Santa Maria - Rodrigues, Rosane Sória (2024)
The University Housing Program in Brazil is part of the National Student Assistance Policy and aims to improve academic performance and contribute to the graduation of higher education students, as well as promoting permanence conditions for resident students, beneficiaries of the program. Therefore, the objective of this research was to evaluate the impact of university housing on the performance, permanence, retention and dropout of residents of the University Student Houses (CEU) at the Federal University of Santa Maria. Using reports provided by the Education Information System (SIE), the two groups of students assisted by the Socioeconomic Benefit Program were compared, in a quantitative research approach. The sample included a total of 4,710 students: the resident group (treatment) with 2,647 students and the non-resident group (control) with 2,063 students. The impact of the University Student House was analyzed using three outcome variables: overall student average, percentage of failures and abandonment/evasion and the covariates are related to the characteristics of the students, their families and area of knowledge. The data were estimated using the Propensity Score Matching technique. The results indicated that, in general, the fact that the student lives at CEU increases the percentage of failures and may have an indirect effect on the total time and delay in completing the undergraduate course and that the probability of abandonment/evasion is greater for younger students residing at CEU compared to older students. Therefore, it was found that participation in the housing program did not have a statistically significant impact on the academic performance index, compared to non-residents. Looking to the future and taking into account the scarcity of research that deals with the topic in question, it is necessary to expand and deepen studies that cover the topic of student housing, as well as the identification of the diversity of factors that directly affect permanence, dropout and completion of residents. And finally, it is reiterated that despite the problems highlighted, and the possible need to reevaluate the compensation required to remain in the student housing program, this undoubtedly represents an essential mechanism for promoting social equality, without which students in a situation of social vulnerability, they would not be able to remain in higher education.